(untitled) (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2022)
The objective of this research is to promote scientific research for the area of Cañaverales’s Spring, department of La Guajira (Colombia), as a new strategy for socioeconomic development, which can become a natural scenario for the development of geotourism for geoconservation purposes, attracting the attention of tourists from the use of the elements of geological heritage as a novel strategy for the socioeconomic promotion of the region. Methodologically it consists of two phases, the first one based on the search, compilation and exhaustive review of national and international publications in different academic and scientific databases; the second phase was based on field work where photographic records were taken, species sampling (flora and fauna); in addition, the geological sites of interest, located in the south of the department of La Guajira (Colombia), were inventoried, characterized, evaluated and qualitatively assessed. The Cañaverales’s Spring Protected Forest Reserve corresponds to a tropical dry forest ecosystem rich and diverse in its flora and fauna, whose particularity lies in the presence of outcrops of crystalline groundwater, which supplies the community for its activities; so its aesthetic, cultural and environmental value should be protected through geo-education and geotourism activities.